Challenges in Achieving Gender Equality in Architecture (EAAE Annual Conference Proceedings, 2023)
The formation of qualified environments requires evaluation of sociocultural as well as physical aspects. The improvement of the physical quality of the environment means the production of safe, useful, and healthy interior and exterior spaces. In this context, sustainability, resilience and biodiversity have to be carefully considered in relation to the protection of the environment. However, in order for societies to continue their existence and to be reproduced, the environment has to bear meanings which reflect the values and needs of the users, and it has to be suitable for social changes.